Pengaruh Upah Kerja Terhadap Motivasi Tenaga Kerja: (Studi Kasus PT. Satria Bahari Utama Ende) - Damianus Tola (Ekspektasi: Jurnal Pendidikan Ekonomi, 2017)
The results showed that: (1) Wages are on holiday on the motivation of workers unloading the goods at PT. Satria main Bahari Ende No effect is shown by the multiple linear regression equation b1 F_ (count) greater than 3.145 of F_ (table) 3.20; (2) The provision of wages on a normal day on the motivation of workers unloading the goods at PT. Satria main Bahari Ende have no effect this is indicated by multiple linear regression equation b2 F_ (count) is smaller -.0,317 of F_ (table) 3.20; (3) The results of data analysis showed that there was no effect of the wage system of work motivation (Y) which is indicated by the test of significance ? = 0.5% and 0.1% with degrees of freedom (df) = 46 obtained F_tabel> F_hitung> F_ ( table) = shown in figure 3.20> -12.66> 5.10. To maintain the existing wage system, PT. Satria main nautical should maintain the existing remuneration and motivation necessary to further improve their bonuses in the form of THR in accordance with the ability of the company.